Exploring the risk factors associated with hypertension in children: A systematic review - Annisa, Nadiya Sahara; Haryanto, Joni; Kristiawati, Kristiawati (Universitas Airlangga, 2024)
Introduction: Hypertension in children is increasingly becoming a global concern due to its impact on long-term health. This is influenced by several risk factors that can favor the occurrence of hypertension in children. The purpose of this systematic review is to determine the risk factors that can affect the occurrence of hypertension in children.Methods: Searching articles using Medical Subject Heading (MeSH) with keywords of risk factor AND hypertension OR high blood pressure AND children OR child. This research used academic databases, including Scopus, CINAHL, ScienceDirect, and Google Scholar with inclusion criteria. The article discusses the risk factors for hypertension in children aged 6-19 years, no history of autoimmune and hematological disease, articles published in 2018-2023, studies using observational and quasi-experimental designs in English and using The Joanna Briggs Institute (JBI) Critical Appraisal method.Results: This research analyzed a total of seven articles. The risk factors for hypertension that often occur in children include excessive nutritional status, lack of physical activity, family history of hypertension, smoking habits in children, excess sodium consumption, and male gender have a higher risk of hypertension.Conclusion: Obesity has become the dominant factor in hypertension in children. It is recommended that children and adolescents exercise regularly, follow examinations at school or the nearest health facility, and maintain a healthy and regular diet. Keywords: children; hypertension; risk factor